Showing and telling—How directors combine embodied demonstrations and verbal descriptions to instruct in theater rehearsals - Schmidt, Axel; Deppermann, Arnulf (Frontiers in Communication, 2023)
Abstract In theater as a bodily-spatial art form, much emphasis is placed on the way actors perform movements in space as an important multimodal resource for creating meaning. In theatre rehearsals, this usually happens in series of directors’ instructions and actors’ implementations. Directors’ instructions on how to conduct a movement often draw on embodied demonstrations in contrast to verbal descriptions. For instance, to instruct an actress to act like a school girl a director can use depictive (he demonstrate the expected behavior) instead of descriptive (‘can you act like a school girl’) means. Drawing on a corpus of 400 hours video recordings of rehearsal interactions in three German professional theater productions, from which we selected 265 cases, we examine ways to instruct movement-based actions in theater rehearsals. For the present article, we have chosen nine instances, on which we aim to illuminate 1. the difference in using embodied demonstrations versus verbal descriptions to instruct; 2. in which typical ways directors combine verbal descriptions with embodied demonstration in their instructions. First, we ask what constitutes a demonstration and what does it achieve in comparison to verbal descriptions. Using a typical case, we illustrate four characteristics of demonstrations that all of the cases we studied share. Demonstrations 1. are embedded in instructional activities; 2. show and do not tell; 3. are responded to by emulating what was shown; 4. are rhetorically shaped to convey the instruction’s focus. However, none of the 265 demonstrations we investigated were produced without verbal descriptions. In a second step we therefore ask in which typical ways verbal descriptions accompany embodied demonstrations when directors instruct actors how to play a scene. We distinguish four basic types. Verbal descriptions can be used 1. to build the demonstration itself; 2. to delineate a demonstration verbally within an instruction; 3. to indicate positive (what should be done) and negative (what should be avoided) versions of demonstrations; 4. as an independent mean to describe the instruction’s focus additionally to the demonstration. Using a multimodally extended ethnomethodological-conversation analytical approach, we focus on the multimodal details that constitute demonstrations as complex action types.